PENINGKATAN PARIWISATA DAN PERHOTELAN DI PROVINSI RIAU - Lanang Diayudha (Program Studi Hospitality dan Pariwisata, 2017)
Riau is a province on the Island of Sumatera that is adjacent to Singapore and Malaysia. Currently more tourist come to Riau for various purposes. This arrival of tourist becomes a trigger of the hotel growth. By the increasing of the hotel growth, local government needs to organize the tourism sector. It aims to add the time of stay so that the people of Riau get the positive impact from this situation. Because of that reason, we need to know the factors that influence the confidence of investor, mainly in hotel sector.Keywords: hotel growth, tourism sector, confidence of investor